Extending the π-system of Inverted Solvatochromic Phenolate-Based Dyes Shifts Their Inversion Point Due to an Increment in Their Sensitivity to Solvent Polarizability - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Aburto-Bernal, I (Elsevier B.V., 2022)
Two pairs of phenolate-based dyes with a π-connecting system of different lengths were synthesized, and their spectral variations were investigated in pure solvents of variable polarity and methanol-dichloromethane solvent mixtures. All the dyes studied exhibited inverted solvatochromism, and multiparametric analysis of their solvatochromic absorption bands of these dyes revealed that the solvent acidity and polarizability are mainly responsible for this behavior. The extension of the π-connecting system brings out of the shifts of the spectral behavior exhibited by the dyes towards shorter wavelengths with a concomitant displacement of the position where their solvatochromic inversion takes place towards higher solvent polarity due to an increment in the ability of the extended dyes to sense the solvent polarizability, without modifying the specific solute–solvent interactions in the first or the second solvation layer, a result confirmed by theoretical calculations. © 2022 Elsevier B.V.